Decoupling robust control of three-link direct drive robot arm - Zhang, C. (2013)
This paper introduces the mechanical structure of a three-link direct drive SCARA for wafer handling application. The dynamic modeling of the presented SCARA is derived and the coupling effect of the system is studied. A decoupling method based on computed torque control is employed in the implementation. Robust control is applied to design the SISO controllers after the system is decoupled. The experimental test results demonstrate satisfying dynamic, settling and static performances by utilizing the decoupling robust control.